Primary sclerosing lipogranuloma: an unusual scrotal mass - Praveen Singam; Leny Suriyani; Christopher Ho; Goh Eng Hong; Zulkifli Zainuddin (Libyan Journal of Medicine, 2010)
Sclerosing lipogranuloma (SLG) of the male external genitalia is a rare benign condition presenting as subcutaneous masses. The underlying pathological process is a granulomatous reaction of fatty tissue in this area. The cause of this is unclear but hypothesis stems around the pathogenesis of exogenous lipid degeneration from injection of foreign bodies such as paraffin for penile augmentation. However, endogenous lipid degeneration from other various causes such as infection, trauma, and allergic mechanisms has also been reported. We present the case of a 40-year-old man with primary SLG of the external genitalia. Literature review on the treatment strategies are addressed and discussed.